Association of spinal inclination with physical performance measures among community‐dwelling Japanese women aged 40 years and older. Issue 4 (26th December 2012) - Abe, Yasuyo; Aoyagi, Kiyoshi; Tsurumoto, Tadao; Chen, Chih‐Yu; Kanagae, Mitsuo; Mizukami, Satoshi; Ye, Zhaojia; Kusano, Yosuke
<x xml:space="preserve">Abstract</x> Aim Spinal inclination assesses spinal posture as a whole. However, the association between spinal inclination and physical performance has not yet been fully elucidated. Therefore, this study aimed to explore the association of spinal inclination with physical performance measures. Methods The participants were 107 Japanese women aged 40–84 years. Spinal posture was assessed as inclination to a perpendicular line by using a computer‐assisted device. Increased inclination value means forward inclination of the spine. Physical performance was measured by using the following methods: 6‐m walking time, chair stand time, functional reach, Timed Up & Go Test, and grip strength. Information on participants' comorbidities, osteoporosis, knee joint pain, back pain, falls in the previous year, regular exercise and usage of non‐steroidal anti‐inflammatory drugs (NSAIDs), was also collected. Results Pearson's correlation analysis showed significant associations between spinal inclination and all of the physical performance measures. Pearson's partial correlation analysis adjusted for age showed significant associations of increased inclination with poor physical functioning in 6‐m walking time, chair stand time, functional reach, and Timed Up & Go Test, but not in grip strength. Linear regression analysis adjusted for age, grip strength, number of comorbidities, osteoporosis, knee joint pain, back pain, falls in previous year, regular activity and taking NSAIDs showed that spinal inclination was associated with poor function in 6‐m walking time, chair stand time, functional reach and Timed Up & Go Test. Conclusion Forward spinal inclination was associated with impairment in various physical performance measures. Proper prevention and treatment of underlying disorders should be prompted. Geriatr Gerontol Int 2012; 13: 881–886.